Treatment of mining-influenced water at Malanjkhand copper mine. Issue 52 (7th November 2016) - Tiwari, Onkar Nath; Pradhan, Manoj; Nandy, Tapas
Abstract: The chemical precipitation technique has been successfully utilized to treat the mine water. The copper concentration in mine water was below 50 mg per liter in majority of samples collected for the study. Iron concentration varied between 0.02 and 4.55 mg per liter. It was 0.674–3.83 mg per liter for manganese and fluoride concentration of 0.18–6.6 mg per liter was found. The pH range of mine water was 4.1 and 7.4. The study investigated the effect of pH adjustment and lime dosage on the mine water. Sample after treatment were analyzed for pH, chemical oxygen demand (COD), suspended solids (SS), total dissolved solids (TDS), and copper and fluoride ion concentration. The copper concentration reduction was found to be >99% over a treatment pH range of 8.0–9.5 using lime dosage of 140–170 mg/L at 56% purity of lime but the fluoride removal efficiency was approximately 40% at a treatment pH of 9.0. Thus, the study indicates the requirement of elevated pH (10.5) for better fluoride removal efficiency of 70%. It was also observed that lime with higher purity is better in terms of copper and fluoride removal effectiveness. Finally, the treated water pH (after settlement of sludge) was in the range recommended for discharge in inland surface waters bodies.